Cyclooxygenase-2 Mediated Regulation of E-Cadherin Occurs in Conventional But Not Early-Onset Gastric Cancer Cell Lines - R. Sitarz; R. J. Leguit; W. W. J. de Leng; F. H. M. Morsink; W. P. Polkowski; R. Maciejewski; G. J. A. Offerhaus; A. N. Milne (Cellular Oncology)
Background: COX-2 and E-cadherin, involved in invasion and metastasis, are molecules critical for gastric carcinogenesis. A relationship between them is documented in non-small cell lung and prostate cancer. We present novel evidence of a relationship between COX-2 and E-cadherin expression in gastric cancer.